Doing Good by Doing Well? Microfinance, Self‐Regulation and Borrowers' Over‐indebtedness in the Dominican Republic. (7th September 2016) - Afonso, Joana Silva; Morvant‐Roux, Solène; Guérin, Isabelle; Forcella, Davide
Abstract: The Dominican Republic's microfinance sector is considered to be a solid market where over‐indebtedness prevention best practices are widely and successfully implemented. Relying on qualitative data collection tools and analysis, we identify these 'best practices' as self‐regulation mechanisms, and we show how they fail to fully fulfil their goals in the Dominican market. While financial exclusion supports the idea of a sizable microcredit market, we argue that the focus on growth and high competition strongly jeopardizes the positive social outcomes of microcredit, and that only a paradigm shift within the sector will really change the present situation. Copyright © 2016 John Wiley & Sons, Ltd.